Cassava and Poultry Business: Peri-Urban Trend in Assembling, Processing and Marketing Trade Offs in Kiryateete Village, Hoima Oil City Uganda - Godfrey Alinaitwe (Economit Journal: Scientific Journal of Accountancy, Management and Finance, 2023)
Supply chains are changing rapidly, with transactions increasingly based on chains that involve coordinated links between farmers, traders, processors and retailers. It is against this background that this paper is made and synthesized after a field report analysis of how marketing of cassava and chicken is done at various stages in the supply chain. Emphasis is placed on markets chosen for linkages, on the capacity of the linking traders and consumers, and on the relationship between them. The paper tries to describe and explain the different marketing stages of assembling, transportation, processing and preparation for consumption of cassava and chicken by different smallholder individuals involved. It outlines the challenges and opportunities involved in marketing of these products.